Purification of a Hydrophobic Elastin-Like Protein Toward Scale-Suitable Production of Biomaterials - Haas, Sandra; Desombre, Monika; Kirschhöfer, Frank; Huber, Matthias C.; Schiller, Stefan M.; Hubbuch, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
Elastin-like proteins (ELPs) are polypeptides with potential applications as renewable bio-based high-performance polymers which undergo a stimulus-responsive reversible phase transition. The ELP investigated in this manuscript – ELP[V2Y-15] – promises fascinating mechanical properties in biomaterial applications. Purification process scalability and purification performance are important factors for the evaluation of potential industrial scale production of ELPs. Salt-induced precipitation, inverse transition cycling (ITC) and immobilized metal ion affinity chromatography (IMAC) were assessed as purification protocols for a polyhistidine-tagged hydrophobic ELP showing low temperature transition behavior. IMAC achieved a purity of 86 % and the lowest nucleic acid contamination of all processes. Metal ion leakage did not propagate chemical modifications and could be successfully removed through size exclusion chromatography. The simplest approach using a high-salt precipitation resulted in a 60 % higher target molecule yield compared to both other approaches with the drawback of a lower purity of 60 % and higher nucleic acid contamination. An additional ITC purification led to the highest purity of 88% and high nucleic acid removal. However, expensive temperature dependent centrifugation steps are required and aggregation effects even at low temperatures have to be considered for the investigated ELP. Therefore, ITC and IMAC are promising downstream processes for biomedical applications with scale dependent economical costs to be considered, while salt-induced precipitation may be a fast and simple alternative for large scale bio-based polymer production.